Determinants of dividend payout ratio - Elgammal, Walid (2014)
This paper studies the determinants of the dividends payout ratio. The factors affecting the dividends payout ratio are to be identified. The study focuses only on the cement and construction industry within the MENA region in an attempt to isolate any incoherent behavior. The factors under consideration are: Sales Growth, ROE, ROA, ROS, Debt to Equity Ratio, Firm Size, and Free Cash Flow. Data were collected from official stock exchange markets in addition to annual reports. The study considered all firms that paid dividend in each of the three consecutive years starting from 2010 till 2012. Out of the 123 listed firms that work in cement and construction industry in MENA region, only 19 paid dividends in the three consecutive years 2010-12. Our sample consists of the 19 firms (57 observations) is selected according to purposive sampling. Moreover, the study uses the homogeneous subcategory within the purposive sampling since only similar firms in construction industry had been examined. The outcome of the study provides a vital insight into the determinants of dividends payout ratio of companies in MENA region. The results showed that the Dividend Payout Ratio has a strong and positive relationship with Return on assets and strong but negative relationship with Return on Equity. On the other hand, the results detected weak relationships between Dividend Payout Ratio and Sale Growth, Debt to Equity Ratio, Firm size, and Free Cash Flow. The study suggests that board of directors tend to compensate shareholders and minimize the agency cost by distributing a high portion of profits in form of dividends whenever return on equity decreases. Also, when the performance of the firm improves, and hence return on assets increases, boards of directors are more generous in distributing profits.